Stigma, perceived blame, self‐blame, and depressive symptoms in men with colorectal cancer. Issue 1 (26th September 2011) - Phelan, Sean M.; Griffin, Joan M.; Jackson, George L.; Yousuf Zafar, S.; Hellerstedt, Wendy; Stahre, Mandy; Nelson, David; Zullig, Leah L.; Burgess, Diana J.; van, Michelle
Abstract Background We measured the prevalence of stigma, self‐blame, and perceived blame from others for their illness among men with colorectal cancer (CRC) and examined whether these factors were associated with depressive symptoms, independent of clinical and sociodemographic factors. Methods Self‐administered questionnaires were returned in the fall of 2009 by 1109 eligible male US veterans who were diagnosed with CRC at any Veterans Affairs facility in 2008. Questionnaires assessed stigma, feelings of blame, and depressive symptoms as well as other facets of health, cancer characteristics, and quality and type of medical care. We report the prevalence of cancer stigma, self‐blame, and perceived blame from others. We used multivariate linear regression to assess the association between these factors and a measure of depressive symptoms. Covariates included several measures of overall health, cancer progression, symptom severity, and sociodemographic factors. Results Thirty one percent of respondents endorsed at least one item in a measure of cancer stigma and 25% reported feeling that it was at least 'a little true' that they were to blame for their illness. All three independent variables were associated with depressive symptoms in bivariate models; cancer stigma and self‐blame were significantly associated with depressive symptoms in the multivariate model. Conclusions Cancer stigma and self‐blame are problems for a significant minority of men with CRC and are independent predictors of depressive symptoms. They may represent an important source of stress in men with CRC. Copyright © 2011 John Wiley & Sons, Ltd.